IDENTIFIKASI MEDICATION ERROR FASE PRESCRIBING PADA PASIEN DI IGD ANAK RSUP DR. WAHIDIN SUDIROHUSODO MAKASSAR TAHUN 2020 - Hernawati Basir (Akademi Farmasi Yamasi Makassar, 2022)
Medication error is an actual adverse event that can be prevented during the patient's treatment process. Medication error can occur in the prescribing phase, so the recipe must be complete and clear to avoid mistakes in reading the recipe especially if the patient is still children. Because child patients have the function of organs that have not been maximized in terms of drug distribution in the body. The type of research used in this study is a descriptive observation with a cross sectional operational approach in RSUP Dr. Wahidin Sudirohusodo Makassar. From the results of the research has been concluded that the event medication biggest error occurred in the prescribing phase at IGD Anak in May 2020 is the absence of the patient's weight written in the prescription with a percentage of 87.9%, and the smallest occurrence that occurs is not to write the prescription date with a percentage of 1.7%.